Swine carcasses classified by degree of exudation and marbling content - Bertol, Teresinha Marisa; Coldebella, Arlei; Santos Filho, Jonas Irineu dos; Guidoni, Antonio Lourenço (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to develop and evaluate prediction equations, based on measurements obtained on the slaughter line, for carcass classification according to the degree of exudation and the content of marbling. A total of 747 pig carcasses originated from 27 producers were randomly selected on the slaughter line at two slaughterhouses, constituting representative samples from each one. Hot carcass weight, loin depth, back fat thickness, and pH and temperature 45 min after slaughter were used to generate the equations. The carcasses were classified as normal or exudative for drip loss of loin and ham, and as acceptable or undesirable for marbling content. For drip loss of loin and ham, respectively, the overall correct classification of the carcasses was 87.3 and 76.8%, using the discriminant functions, for both categories. For marbling, the overall correct classification was 67.2%, and only 69% of the carcasses were correctly classified as acceptable (marbling >1). The equations developed based on the measurements obtained on the slaughter line allow classifying swine carcasses with high accuracy, according to the degree of exudation, but not with the content of marbling.